2018
DOI: 10.1158/1078-0432.ccr-16-3187
|View full text |Cite
|
Sign up to set email alerts
|

The Airway Transcriptome as a Biomarker for Early Lung Cancer Detection

Abstract: Lung cancer remains the leading cause of cancer-related death due to its advanced stage at diagnosis. Early detection of lung cancer can be improved by better defining who should be screened radiographically and determining which imaging-detected pulmonary nodules are malignant. Gene expression biomarkers measured in normal-appearing airway epithelium provide an opportunity to use lung cancer-associated molecular changes in this tissue for early detection of lung cancer. Molecular changes in the airway may res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 71 publications
0
19
0
Order By: Relevance
“…However, importantly, tumor cells originate from the same cell subtypes of one or more of the original healthy cells in a tissue. Numerous methods exist for classifying (or diagnosing) a whole tissue biopsy as either cancerous or non-cancerous based on DNA genotyping [42], transcriptome profiling [43, 44], or histochemistry [45, 46]. Most of these methods work well, but are unable to accurately classify heterogeneity at a cellular level, and do not work if the percentage of tumor cells in a biopsy is small.…”
Section: Resultsmentioning
confidence: 99%
“…However, importantly, tumor cells originate from the same cell subtypes of one or more of the original healthy cells in a tissue. Numerous methods exist for classifying (or diagnosing) a whole tissue biopsy as either cancerous or non-cancerous based on DNA genotyping [42], transcriptome profiling [43, 44], or histochemistry [45, 46]. Most of these methods work well, but are unable to accurately classify heterogeneity at a cellular level, and do not work if the percentage of tumor cells in a biopsy is small.…”
Section: Resultsmentioning
confidence: 99%
“…59 RNA Airway and Nasal Signature. On the basis of the "field of injury" paradigm, 60 airway epithelial gene expression has been developed as a diagnostic biomarker for lung cancer. The initial studies focused on bronchial airway epithelial cells obtained by endobronchial brushings of the mainstem bronchus.…”
Section: Molecular Biomarkers For Lung Cancer Screeningmentioning
confidence: 99%
“…Indeed, there is some evidence that nontumor adjacent cells share some molecular characteristics with tumor cells. In this context, it has been recently demonstrated that most genetic alterations expressed in smoker patients are not only found in bronchial but also in the nasal epithelium [31]. Thus, LC-associated gene expression assessment in nontumor respiratory epithelium may represent a promising field of development to optimize LC risk evaluation and, thus, to better understand its pathogenesis [31].…”
Section: Lung Cancer Screening Can Be Improvedmentioning
confidence: 99%